ПРЕДМЕТ ТА ЗМІСТ УГОДИ ПРО СПІВПРАЦЮ МІЖ ПІДОЗРЮВАНИМ (ОБВИНУВАЧЕНИМ) ТА ПРОКУРОРОМ У КРИМІНАЛЬНОМУ СУДОЧИНСТВІ УКРАЇНИ - Сіроткіна, Марія Вячеславівна (SUPREMANCE OF LAW, 2018)
The article reveals the concept, subject and content of the agreement about cooperation in criminal judiciary. Based on the analysis of the current legislation of Ukraine, the author concludes that the agreement about cooperation between the suspect and the prosecutor is a kind of compromise, the essence of which is to fulfill obligations to facilitate the detection of criminal offenses committed by others in exchange for mitigation of punishment, committing. In this regard, the need to consolidate the cooperation agreement as an independent type of agreement in criminal judiciary is justified. To resolve the question of whether the cooperation between the suspect and the prosecutor is in the nature of an agreement, the concept of a crime as a criminal conflict is taken into account, the resolution of which in criminal judiciary resembles the resolution of a civil dispute in civil proceedings. This approach allowed the author to draw an analogy between an amicable agreement in civil judiciary and an agreement about cooperation in criminal judiciary, defining the latter as a procedural agreement. In order to improve the legal regulation of relations about cooperation, the author considers it necessary to take into account the scientific provisions that determine the main features of the agreement, its subject and content. The article substantiates that the subject of the cooperation agreement is the mutual obligations of the parties that concluded it. The suspect must take actions aimed at exposing a criminal offense committed by another person. Among them: testifying about the specific circumstances of the case; active participation in investigative actions; presentation of evidence to expose a criminal offense committed by another person. The prosecutor, in turn, is obliged to submit an agreement for approval to the court, to insist on the application by the court of such a measure of punishment as stipulated in the agreement with the suspect, to take measures to mitigate the precautionary measure and ensure the safety of the suspect and the members of his family.